E-105 Predictors of excellent outcomes post thrombectomy in large vessel occlusion with mild strokes. (22nd July 2019) - Pandhi, A; Goyal, N; Tsivgoulis, G; Malhotra, K; Ishfaq, M; Frohler, M; Spiotta, A; Anadani, M; Psychogios, M; Maus, V; Siddiqui, A; Waqas, M; et al.
Abstract : Background: As the randomized controlled trials excluded the patients with emergent large vessel occlusion (ELVO) strokes with low NIHSS <6, the efficacy and safety of mechanical thrombectomy (MT) in this cohort is lacking. We sought to explore the predictors of excellent outcomes after MT in this international multicenter study. Methods: Stroke patients with ELVO and NIHSS <6 treated with MT were identified from 16 high volume endovascular stroke centers over a 4 year period (2013–2017). Predictors of excellent outcomes post MT were evaluated. Baseline demographic, clinical and procedural variables were obtained. Successful recanalization was defined as mTICI 2b and 3. Excellent outcomes are defined as modified Rankin Stroke (mRS) scale of 0–1 at 3 months. Results: Total of 146 patients with low NIHSS ELVO were included in the study. Of those, 95 (65%) patients (48% male, 71% Caucasians, mean NIHSS 3.6 ±1.3) had excellent outcome (mRS 0–1), while remaining 51 (35%) patients (57% male, 72% Caucasians, mean NIHSS 3.8 ±1.4) had poor outcome (mRS 2–6). The patients who had excellent outcome had lower age at presentation [years, mean (SD) 61.6±17.2 vs. 68.9±18.6; p: 0.012], higher rates of successful recanalization [91.2% vs. 74%; p: 0.012], and shorter groin puncture to recanalization time [minutes, mean (SD): 43.4 ±27.3 vs. 60.4 ±41.5, p=0.008) compared to poor outcome group. The mean baseline ASPECTS tended to higher in excellent outcome group (9.3 ±1.0 vs. 8.9±1.3, p=0.08). In multivariable analyses after adjustment for potential confounders, lower age (OR: 0.96, 95% CI 0.93–0.99, p=0.034), shorter groin puncture to recanalization time (OR: 0.97, 95% CI 0.96–0.99, p=0.003), and successful recanalization (OR: 11.2, 95% CI 1.5–80.4, p=0.016) were independent predictors of excellent outcome at 3 months. Conclusions: Our retrospective multi-center study demonstrates that lower age, shorter groin puncture to recanalization time and successful recanalization were independent predictors of excellent outcomes post MT in ELVO patients with NIHSS <6. Disclosures: A. Pandhi: None. N. Goyal: None. G. Tsivgoulis: None. K. Malhotra: None. M. Ishfaq: None. M. Frohler: None. A. Spiotta: None. M. Anadani: None. M. Psychogios: None. V. Maus: None. A. Siddiqui: None. M. Waqas: None. P. Schellinger: None. M. Groen: None. O. Saeed: None. C. Krogias: None. D. Richter: None. M. Saqqur: None. P. Bermejo: None. M. Mokin: None. R. Leker: None. A. Katsanos: None. G. Magoufis: None. K. Psychogios: None. V. Lioutas: None. M. VanNostrand: None. V. Sharma: None. M. Paciaroni: None. A. Rentzos: None. H. Shoirah: None. J. Mocco: None. D. Hoit: None. L. Elijovich: None. A. Alexandrov: None. A. Arthur: None.